THE ART OF CONNECTING CULTURES: HOW MUSIC CAN NURTURE MUTUAL RESPECT (Religious dialogue and cooperation, 2024)
How can we proactively rehearse a collective sense of humanity, and let go of the focuson our cultural differences as an obstacle? The dissimilarity of people has become a popular reasonfor social exclusion, regularly leading up to hate speech, dehumanization and destruction. This essaydemonstrates how community music programs can create a sense of intercultural community,both between musicians as throughout all participants including teachers, family and the audience.Firstly, the relevance of collective music making is discussed along with the ideas of RichardSennett on music and mutual respect, and of Alicja Gescinska on feeling at home in music. This createsan interdisciplinary framework of political and philosophical theories, which is expanded bypsychological research. To maintain respect between people from different cultural and religiousbackgrounds is not something that tends to be stimulated in the individualistic belief systems ofWestern commercialisation and competitive education systems. Where do our children and futuregenerations practice teamwork, intercultural communication and a curiosity for cultures thatreach beyond their own belief systems? Arts in general, and music in particular, can and shouldoffer fertile grounds for these learnings through working together, active listening and practices incollective resonation. To illustrate these arguments, examples such as the El Sistema Europe YouthOrchestra (SEYO) and Musicians Without Borders will be discussed to show the serious potential ofmusic in the nurturing of mutual respect in an intercultural society. In order to enable such powerfulprojects, it is essential that governmental institutions, policymakers and academicians supportthe sustainability and growth of community music programs, to make them widely accessible inareas which could benefit from proactive, creative practices in intercultural and religious dialogue.
Keywords: mutual respect; listening; intercultural society; democratic groove